Early detection of bilateral cataracts in utero may represent a manifestation of severe congenital disease. Issue 7 (3rd June 2016) - Trkova, Marie; Hynek, Martin; Dudakova, Lubica; Becvarova, Vera; Hlozanek, Martin; Raskova, Dagmar; Vincent, Andrea L.; Liskova, Petra
Abstract : We observed bilateral cataracts on second trimester ultrasound, in two consecutive pregnancies, with no other structural defects detected. The parents were unrelated and had no family history for the disease. The first pregnancy was terminated in week 22. Copy number variation analysis revealed, in both the aborted fetus and the mother, a 495 kb duplication at 22q11.23 encompassing CRYBB3 and CRYBB2, and not present in variation databases. In the second pregnancy, lens hyperechogenicity was detected by ultrasound at week 13 and 4 days. The identical duplication at 22q11.23 was found in the fetus and considered as possibly pathogenic. At weeks 22 and 30, smaller orbit measurements were elucidated on ultrasound, raising concerns as to the underlying molecular genetic cause, necessitating further investigation. Whole‐exome sequencing, using DNA of the first fetus, was performed shortly after the birth of a male child, and two truncating RAB3GAP1 mutations were detected: c.538G>T; p. (Glu180*) and c.943C>T; p. (Arg315*). Neither mutation has been previously reported to be disease‐causing; however, evaluation in the context of previously published literature indicated their deleterious nature, implying a clinical diagnosis of Warburg micro syndrome or Martsolf syndrome. Sanger sequencing confirmed segregation of the two mutations within the family, consistent with autosomal recessive inheritance. The child born from the second pregnancy showed features typical of Warburg micro syndrome, with the exception of microcephaly, at age 31 months. © 2016 Wiley Periodicals, Inc.